2019
DOI: 10.1016/j.ygyno.2019.04.682
|View full text |Cite
|
Sign up to set email alerts
|

Expanded validation of the EPIC bowel and urinary domains for use in women with gynecologic cancer undergoing postoperative radiotherapy

Abstract: Objective: Women with endometrial or cervical cancer at risk for recurrence receive postoperative radiation therapy (RT). A patient reported outcomes (PRO) instrument to assess bowel and urinary toxicities is the Expanded Prostate Cancer Index Composite (EPIC), which has been validated in men with prostate cancer. As this instrument specifically measures bowel toxicity and the degree to which this is a problem, it was used in NRG Oncology/RTOG 1203 to compare intensity modulated RT (IMRT) to standard RT. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Our findings need to be validated in studies with larger cohorts. Despite these limitations, these patients received current standard treatments with adequate follow-up, and their outcomes are comparable to previous studies [ 6 , 7 , 8 ].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our findings need to be validated in studies with larger cohorts. Despite these limitations, these patients received current standard treatments with adequate follow-up, and their outcomes are comparable to previous studies [ 6 , 7 , 8 ].…”
Section: Discussionsupporting
confidence: 72%
“…However, we found that the PRO-CTCAE, PG-SGA, and body composition changes were not different between patients with chemotherapy and without chemotherapy. The possible explanation might be that patients in this study received intensity-modulated radiotherapy that can deliver focused radiation to the pelvic lymphatic regions while minimizing doses to the bowel and therefore lowering the GI toxicity [ 6 , 7 , 8 ]. However, it should be noted that the GI toxicity of pelvic radiotherapy is mainly abdominal pain and diarrhea, while nausea and vomiting are mainly related to chemotherapy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPIC was later validated for use in a female population. 134 There are also sexual, hormonal, and health-related quality of life domains of EPIC. The different domains can be used separately from each other.…”
Section: Patient-reported Symptomsmentioning
confidence: 99%
“…It can be used for both male and female subjects, and it covers both qualitative and quantitative symptoms. 134 EPIC only requires input from the patient and can hence be used for long-term evaluation without clinical assessment. Furthermore, EPIC is validated and has been used for over 20 years.…”
Section: Does Hbot Help At All? -Paper Imentioning
confidence: 99%